1986
DOI: 10.1093/infdis/154.4.665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Concentrations of Amphotericin B on Candida albicans

Abstract: Because sublethal concentrations of antibodies can have important effects on bacteria and may aid host defenses, even in the absence of direct microbial killing, the effect of brief sublethal exposures to amphotericin B on Candida albicans blastoconidia was evaluated. Amphotericin B (0.01-1.0 micrograms/ml for 60 min) inhibited germ tube formation and yeast adherence to both serum-coated plastic surfaces and fibrin matrices. These effects were not reversed by cation (K+ or Mg++) supplementation. Amphotericin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
11
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
8
11
1
Order By: Relevance
“…Thus, a concentration of 0.5 ,ug/ml was subfungicidal against a susceptible C. albicans isolate for which the MIC was 0.15 ,ug/ml. These observations were in accord with previous data of Nugent and Couchot (30) and van Etten et al (47) and have also been reported by us previously (24,25). As discussed elsewhere (25), they also provide an explanation for the fact that high concentrations of amphotericin B in plasma (1 to 2 jxg/ml) need to be reached in order for the polyene to exert its curative effects in systemic fungal infections.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, a concentration of 0.5 ,ug/ml was subfungicidal against a susceptible C. albicans isolate for which the MIC was 0.15 ,ug/ml. These observations were in accord with previous data of Nugent and Couchot (30) and van Etten et al (47) and have also been reported by us previously (24,25). As discussed elsewhere (25), they also provide an explanation for the fact that high concentrations of amphotericin B in plasma (1 to 2 jxg/ml) need to be reached in order for the polyene to exert its curative effects in systemic fungal infections.…”
Section: Discussionsupporting
confidence: 92%
“…As confirmed by microscopy, increases in particle size as detected by flow cytometry were invariably the result of germ tube formation and cell aggregation, events that we equated with absence of fungistasis. As a reference for fungistasis, samples were spiked with 0.5 ,ug of amphotericin B per ml, since this concentration of the drug is subfungicidal in whole serum but inhibits germ tube formation (24,25,30,47) We ascertained that our strain of C. albicans required MICs of fluconazole and 5-fluorocytosine typical of those of susceptible yeasts when tested with conventional procedures in serum-free media. When these two agents were tested in the presence of serum, however, neither was found to be able to inhibit germ tube formation and cell aggregation (an example for fluconazole is given below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular efficacies of the antifungal agents were determined in terms of inhibition of germ tube formation as well as effective killing of C. albicans intracellularly. With AmB, inhibition of the development of germ tubes was found at concentrations lower than those required for killing of intracellular C. albicans, which has also been reported by others (25,26,38). After an increase in the ratio of infection, slightly increased AmB concentrations were required to obtain both effects.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the two lowest concentrations were below the MIC for the organism and demonstrated an impact on gene expression for each of the three genes. Previous studies with both triazoles and polyenes have demonstrated sub-MIC effects using different biologic end points (32,33,39). One explanation for the discrepancy between in vitro and in vivo investigations of the triazole postantifungal effect has been unavoidable sub-MIC exposures which are present in the latter study design (3,16).…”
Section: Discussionmentioning
confidence: 97%